Chemical Mixture Calculator - A novel tool for mixture risk assessment. (June 2021) - Boberg, Julie; Bredsdorff, Lea; Petersen, Annette; Löbl, Nathalie; Jensen, Bodil Hamborg; Vinggaard, Anne Marie; Nielsen, Elsa
Abstract: Humans are continuously exposed to complex chemical mixtures from foods and the environment. Experimental models in vivo and in vitro have increased our knowledge on how we can predict mixture effects. To accommodate a need for tools for efficient mixture risk assessment across different chemical classes and exposure sources, we have developed fit-for-purpose criteria for grouping of chemicals and a web-based tool for mixture risk assessment. The Chemical Mixture Calculator (available at www.chemicalmixturecalculator.dk) can be used for mixture risk assessment or identification of main drivers of risk. The underlying database includes hazard and exposure estimates for more than 200 chemicals in foods and environment. We present a range of cumulative assessment groups for effects on haematological system, kidney, liver, nervous system, developmental and reproductive system, and thyroid. These cumulative assessment groups are useful for grouping of chemicals at several levels of refinement depending on the question addressed. We present a mixture risk assessment case for phthalates, evaluated with and without contributions from other chemicals with similar effects. This case study shows the usefulness of the tool as a starting point for mixture risk assessment by the risk assessor, and emphasizes that solid scientific insight regarding underlying assumptions and uncertainties is crucial for result interpretation. Graphical abstract: Image 1 Highlights: Chemical mixture risk assessment made possible using novel online tool. Suggestions for grouping based on toxic effects on six target organs or systems. Case: Mixture risk assessment for phthalates and chemicals with similar effects.